ANALISIS KEJADIAN DIARE DENGAN FAKTOR-FAKTOR SANITASI LINGKUNGAN DAN PERILAKU CUCI TANGAN DI WILAYAH KERJA PUSKESMAS KENALI KABUPATEN LAMPUNG BARAT - , YUNG EKO UTOMO, Dra. Susi Iravati, Apt., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Diarrhea causes 1.8 million deaths each year mostly in development countries. In Lampung Barat Regency, the incidence rate of diarrhea cases of 2007 - 2012 period was fluctuative and at above 5 year ages group was higher than toddlers. That is why, this research is necesarry to be done because of the increasing of diarrhea cases which usually occurs among toddlers. Objective: This study is aimed to determine the association of environmental sanitation factors and handwashing behavior with diarrheal incidence in the Kenali Health Center, Lampung Barat Regency. Methods: This study is survey an analytical of case control study design. The study is conducted on above 5 (five) years old group of diarrhea patients with 69 case samples and 69 control samples, associated with environmental sanitation factors (clean water, latrines, sewerage) and hand-washing behavior. Univariate analysis of the data uses descriptive techniques percentages, bivariate analysis uses cross tabulation and Chi-square test and multivariate analysis uses logistic regression with Î± = 0.05. Results: Statistical test results shows no associated between the factors of environmental sanitation (clean water, latrines, sewerage) and handwashing behavior with diarrheal disease in the age group above 5 (five) years.